Enhancing Children’s Critical Thinking through an Augmented Reality Application: A Digital Solution for Early Childhood Education - Rinakit Adhe, Kartika; Safitri, Dhian Gowinda Luh; Matheos Lasarus Malaikosa, Yes; Dorlina Simatupang, Nurhenti; Fauziddin, Mohammad (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2025)
Early childhood education in Indonesia continues to encounter significant challenges in fostering critical thinking skills, particularly in under-resourced environments with limited access to adaptive learning technologies. This study investigates the effectiveness of a digital learning model that integrates Augmented Reality (AR) and Artificial Intelligence (AI) to enhance critical thinking among young children. The model, called SMARP (Storytelling, Modifying, Accessible, Real-time, and Promoting), was developed using a Research and Development (R&D) approach based on the 4D model: Define, Design, Develop, and Deploy. The study involved 32 kindergarten students from TK Nada Ashobah in Surabaya, divided into two groups: Class B2 (experimental) and Class B1 (control). The experimental group used an AR–AI-based application, while the control group followed conventional instruction. Data collection included classroom observations, teacher interviews, and critical thinking pre- and post-tests. Statistical analysis using paired sample t-tests and normalized gain (N-gain) scores showed a significant improvement in the experimental group (N-gain = 0.845, categorized as high), while the control group recorded minimal gains (N-gain = 0.0015). The AR–AI model enabled immersive learning through 3D simulations, narrative interaction, and real-time feedback, which promoted observation, analysis, and decision-making. Furthermore, AI features supported personalized learning pathways, increasing student autonomy and engagement. These findings affirm the potential of AR and AI to improve foundational cognitive abilities in early childhood education. The study highlights the need for context-responsive digital pedagogy and recommends comprehensive teacher training and infrastructure support to ensure sustainability. Future research should explore the model’s scalability, long-term impact, and adaptability across diverse educational settings.